The Performance of Visible Light Communication Bit Error Rate with Power Allocation Strategy - MARSUKI, AMINAH INDAHSARI (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Visible Light Communication (VLC) is a communication system that uses visible light as its transmission medium to transmit information signals with Light Emitting Diode (LED) and LASER light sources using visible light between 400 THz (375 nm) to 800 THz (780 nm). VLC has several advantages over the use of radio frequencies in a system. Performance analysis is needed to prove these advantages. Performance analysis was carried out using a mathematical computational simulation using google colab with the python programming language. By taking into account the power allocation (?) strategy in the form of gain ratio power allocation (GRPA) and static power allocation (SPA). The interesting thing from this research is that the power allocation in the VLC system greatly influences the resulting performance. So, it can be locked that the SPA power allocation strategy can be adjusted by producing ?? = 1 and finding the optimal BER value in the range of 10-6 to 10^-3.